GYROTRONES WITH CONE-SHAPED RESONATORS - S. V. Kolosov; I. E. Zaitseva (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2020)
In this paper we compared the efficiency of the cylindrical, conical, and biconical types of gyrotron resonators. Based on the results of comparing the three studied variants of gyrotron profile, it was concluded that the regular-type profile is the least efficient. This type of a resonator made it possible to achieve the level of efficiency of only 23 %, which can be increased in the regular-waveguide gyrothrons only through several modes or by recovering the electrons on the collector. The medium efficiency option is the biconical profile of the resonator. Its efficiency accounted for 42 %. Through a scientific study we revealed an increase in the efficiency for gyrotrons with conical resonators from 23 to 50 % in the TE01 wave. It is worth mentioning that obtaining such efficiency requires phase grouping of the electrons in an increasing high-frequency field by means of an electromagnetic field with further selection of energy from the electron beam in a strong decaying electromagnetic field. The efficiency of 50 % exceeds significantly that of a gyrotron with a regular cavity profile of ~30 %. The gyrotron efficiency for a waveguide profile with a conical resonator and with recovery on the collector can reach 80 %. To carry out the calculations, the KEDR software package was used, and the optimization of the gyrotron parameters, in particular, was carried out using the GYRO-K software. This software has several advantages over other similar options based on the “PIC” code. GYRO-K makes it possible to obtain a high convergence rate when solving boundary value problems, as well as to solve the problem of optimizing the waveguide profile of gyroresonance devices with an acceptable computational burden. Conical cavity gyrotrons can be widely used in industry to create effective gyrotrons for spectroscopy, diagnostics of various media, and for technological needs.